EVALUATION OF BROILER CHICKEN MEAT THAT HAS BEEN SMEARED WITH CLOVE FLOUR (Syzygium aromaticum) FOR PERIOD OF TIMES - N. N. N., Mikariana; Miwada, I N. S.; Lindawati, S. A. (Jurnal Peternakan Tropika; Vol 9 No 2 (2021): Vol. 9 No. 2 Tahun 2021; May - August, 2021)
This study aims to determine the condition of the physical quality and total microbes in broiler meat smeared with clove powder with a concentration of 0.75% of the meat weight during storage. This study used a completely randomized design (CRD) with 4 treatments, namely 5 hours (P1), 10 hours (P2), 15 hours (P3), 20 hours (P4) and 3 replications. The variables observed were total microbes, moisture content, water binding capacity, and pH value. Data analysis used variance (ANOVA) and Duncan's Multiple Range Test (DMRT). The results showed that the pH value of the meat for 15 hours (4,53) had a significant effect (P <0.05) lower than storage for 5 hours (5,08), 10 hours (4,93), and 20 hours (4,94). The total microbes of the meat for 5 hours (1,2 x 10 6 cfu/g), 10 hours (4,1 x 10 8 cfu/g), 15 hours (9,04 x 10 8 cfu/gr), and 20 hours (5,66 x 10 7 cfu/g) showed the difference was not significant (P> 0,05). The water-holding capacity and moisture content of the meat showed no significant differences (P> 0,05). The conclusion of this study is that the storage of meat affects the pH value, but does not affect the water holding capacity, moisture content and is unable to inhibit total microbial growth.   Key words: clove powder, broiler meat, storage time, physical quality, total microbes